Changes in Volume of Subregions Within Basal Ganglia in Obsessive–Compulsive Disorder: A Study With Atlas-Based and VBM Methods - Chen, Jiaxiang; Tian, Chong; Zhang, Qun; Xiang, Hui; Wang, Rongpin; Hu, Xiaofei; Zeng, Xianchun (Frontiers in Neuroscience, 2022)
Background: The studies on volume changes of basal ganglia in obsessive-compulsive disorder (OCD) commonly use voxel-based morphometry (VBM) method, however, Atlas-based method used in such research has not been reported. Atlas-based method has lower false positive rate compared with VBM method, thus has advantages partly. Objectives: The current study aimed to detect the volume changes of subregions within basal ganglia in OCD using Atlas-based method, and compare the results with that of VBM method. What’s more, we explored the influence of software used in Atlas-based method on the volumetric analysis of basal ganglia. Methods: We analyzed the brain structure images of 37 OCD patients and 41 healthy controls (HCs) using VBM method, Atlas-based method based on Statistical Parametric Mapping (SPM) software or Freesurfer software, to find the areas with significant volumetric variation between the two groups, and calculated effects size of theses areas. Results: VBM analysis revealed significantly increased volume of bilateral lenticular nucleus in patients compared to HCs. Atlas-based method based on SPM showed increased volume at trend level of right globus pallidus and left dorsolateral putamen in patients. In contrast, Atlas-based method based on Freesurfer revealed significantly increased volume of left globus pallidus in patients. And the largest effect size of volumetric variation was revealed by Freesurfer analysis. Conclusions: This study showed that the volume of bilateral lenticular nucleus significantly increased in patients compared to HCs, especially left globus pallidus, which was in accordance with the previous findings. In addition, Freesurfer is better than SPM and a good choice for Atlas-based volumetric analysis of basal ganglia. However, the advantages and disadvantages between Atlas-based method and VBM method in basal ganglia volume analysis are still unclear, and needs further studies.